2007
DOI: 10.4103/0253-7613.33433
|View full text |Cite
|
Sign up to set email alerts
|

Lantadene A-induced apoptosis in human leukemia HL-60 cells

Abstract: of apoptosis is an efficient method of treating cancer. [7] Triterpenoids represent a diverse class of natural products. Recently, pentacyclic triterpenoids have been described to induce apoptosis in different cell types. [8] Lantana camara L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 0 publications
1
37
0
Order By: Relevance
“…Apoptosis is a physiological process characterized by chromatin condensation, membrane blebbing, cell shrinkage and DNA fragmentation (Sharma et al 2007). Cytotoxic assay resulted several cytogenetic aberrations having features indicative of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is a physiological process characterized by chromatin condensation, membrane blebbing, cell shrinkage and DNA fragmentation (Sharma et al 2007). Cytotoxic assay resulted several cytogenetic aberrations having features indicative of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Mahato et al 76 isolated a novel flavonol glycoside, named camaraside (12), an anti-tumor agent from L. camera 76 . In addition, Sharma et al 77 showed that lantadene A (13), a torpedoed component of L. camera, induced concentration and time-dependent inhibition of HL-60 cell proliferation by cell cycle arrest in the G0/G1 phase. Lantadene A also induced efficient HL-60 cell apoptosis by activating the caspase-3 pathway, and via the down-and up-regulation of Bcl-2 and Bax expression respectively 77 .…”
Section: Lantana Camara Lmentioning
confidence: 99%
“…8 Thus, modulating or inducing apoptosis might be helpful in cancer therapy or preventions. 7,9 Advanced nanomaterialbased drugs may offer the possibility of new and intriguing opportunities to eliminate the toxicity in human cancer cells.…”
Section: Introductionmentioning
confidence: 99%